2023
DOI: 10.3390/jcdd10020055
|View full text |Cite
|
Sign up to set email alerts
|

Best Practice Guide for Cryoballoon Ablation in Atrial Fibrillation: The Compilation Experience of More than 1000 Procedures

Abstract: Nowadays, the cryoballoon (CB) constitutes an established alternative to radio frequency (RF) ablation for pulmonary vein isolation (PVI), which offers the possibility to isolate the PVs with a single application. Since the introduction of the second-generation CB, we prospectively collected our data to optimize the procedure on >1000 consecutive patients who underwent CB PVI performed in our center. It is expected that subsequent guidelines will suggest first-line PVI through CB in patients with paroxysmal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 87 publications
0
5
0
Order By: Relevance
“…4 Despite over a decade of use the safety profile of cryoablation remains relatively unchanged. [5][6][7][8][9][10] Recently a novel 28 mm cryoballoon system that operates under markedly lower pressure and maintains constant balloon size during cooling has become available for clinical studies. 11 Additionally, a second generation of this novel cryoballoon that allows inflation and ablation at 2 sizes, 28 or 31 mm, has also become available.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Despite over a decade of use the safety profile of cryoablation remains relatively unchanged. [5][6][7][8][9][10] Recently a novel 28 mm cryoballoon system that operates under markedly lower pressure and maintains constant balloon size during cooling has become available for clinical studies. 11 Additionally, a second generation of this novel cryoballoon that allows inflation and ablation at 2 sizes, 28 or 31 mm, has also become available.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, FIRE and ICE showed that cryoablation has a distinct safety profile compared to RF, shifting primary safety events from heat associated pericarditis/perforation to cold associated phrenic nerve impairment and PV stenosis 4 . Despite over a decade of use the safety profile of cryoablation remains relatively unchanged 5–10 …”
Section: Introductionmentioning
confidence: 99%
“…Medical therapy is the first choice, but its effectiveness in reducing the frequency and symptoms of AF recurrence is limited [3]. Ablation is recommended as a second-line AF treatment therapy when medical treatment is ineffective or not tolerated in patients with paroxysmal or persistent AF [5,11,12]. Radiofrequency (RF) ablation and balloon cryoablation can be used to achieve pulmonary vein isolation [13].…”
Section: Discussionmentioning
confidence: 99%
“…Cryoballoon or radiofrequency catheter ablation has emerged as a first‐line treatment of AF with high procedural success (>80%) in high‐volume, experienced centers. 77 , 78 , 79 Given the heterogeneity of the substrate of AF, there are 3 main techniques used for AF ablation: pulmonary vein isolation, LA linear isolation, and LA electrophysiological targets. Hypothesizing that the implanted device creates focal, ectopic electric activity, the third approach is probably the most appropriate.…”
Section: Managementmentioning
confidence: 99%